Attenuation of quasi-Lamb waves in a hydroelastic system elastic plate plus compressible viscous fluid plus rigid wall - Akbarov, Surkay D.; Negin, Mesut (TECHNO-PRESS, 2022)
The paper studies the dispersion and attenuation of propagating waves in the plate+compressible viscous fluid layer system in the case where the fluid layer flow is restricted with a rigid wall, and in the case where the fluid layer has a free face. The motion of the plate is described by the exact equations of elastodynamics and the flow of the fluid by the linearized Navier-Stokes equations for compressible barotropic Newtonian viscous fluids. Analytical expressions are obtained for the amplitudes of the sought values, and the dispersion equation is derived using the corresponding boundary and compatibility conditions. To find the complex roots of the dispersion equation, an algorithm based on equating the modulus of the dispersion determinant to zero is developed. Numerical results on the dispersion and attenuation curves for various pairs of plate and fluid materials under different fluid layer face conditions are presented and discussed. Corresponding conclusions on the influence of the problem parameters on the dispersion and attenuation curves are made and, in particular, it is established that the change of the free face boundary condition with the impermeability condition can influence the dispersion and attenuation curves not only in the quantitative, but also in the qualitative sense.
Keywords: attenuation; compressible viscous fluid; dispersion; Quasi-Lamb waves; Scholte waves; wave propagation; FORCED VIBRATION; LIQUID-LAYER; HOLLOW CYLINDER; MOVING LOAD; PROPAGATION; PRESTRESSES; VISCOSITY; SPECTRUM; Engineering